Role učitele při ovlivňování a zmírňování interetnického napětí ve společnosti - Balvín, Jaroslav (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2015)
The article deals with pedeutology and intercultural problems, and that is teachers’ attitudes towards Roma children and their parents. It is the reaction on discrimination acts on Roma in Czech Republic in the years 2012–2013.